Homage to a gentle giant: Concepts, creativity, and collaboration in our flowing with Elmarie Costandius - Collett, Karen; Verster, Belinda; van den Berg, Caroline (Critical Studies in Teaching and Learning, 2025)
This paper revisits our collaborative process of concept development through the use of the Flow process, introduced to us by Elmarie Costandius. We track and trace her influence on our lives as we re-member and honour how she shaped our intellectual and personal journeys in higher education. Using post-humanist pedagogy and new materialist frameworks, we explored how the Flow process encouraged non-linear thinking, sensory engagement, and experimentation in collaborative learning environments. Our methodology incorporates Jackson and Mazzei's zig-zag concept and Derrida and Barad's notion of hauntology to analyse how past influences continue to shape present and future pedagogical practices. Through collective re-membering and diffractive analysis of notes and artefacts, we documented how this approach promoted awareness and created new possibilities for knowledge creation. Results demonstrate that the Flow process successfully facilitated anti-disciplinary thinking and the assemblage of multiplicities, leading to innovative teaching practices across different disciplines. Ultimately, this paper pays homage to Elmarie and affirms how the collaborative, creative process of concept development can both honour intellectual legacies and open new avenues for innovation and critical engagement in higher education teaching and learning.